The wall–frame interaction effect in CLT-steel hybrid systems - Vogiatzis, Tzanetis; Tsalkatidis, Themistoklis; Efthymiou, Evangelos (Frontiers in Built Environment, 2022)
Behaviour and capacity of cross-laminated timber (CLT) infills built inside steel frames have been given increasing research attention in recent years. It is widely accepted that when the CLT wall panel is built in tight contact with the bounding steel frame to participate in the load sharing, its inherently large in-plane stiffness will attract additional forces to the frame area and change the behaviour of the hybrid system. If not designed properly, the structural integrity of both the infill and the frame will be compromised. It is thus crucial to accurately evaluate the contribution of the infill CLT wall panel to the stiffness and strength of the hybrid system. To that end, a finite element study was performed to investigate the frame-wall interaction effect on the behaviour of hybrid systems. The lateral stiffness, lateral load capacities and hysteretic characteristics of the hybrid systems with frictional and connected interfaces were investigated. The load-sharing effect between the CLT wall and the steel frame was studied. The numerical results showed that the connected models were very effective as the infill absorbed a substantial part of the lateral load, during the initial stages of loading.